التكامل المعرفي وآفاق تجديد الفكر الإسلامي al-Takamul al-Ma’rifi wa Afaq al-Tajdid al-Fikr al-Islamiyi (Integration of knowledge and prospects of reviving Islamic religious thought) - Ahmed Shogar, Ibrahim Adam (IIUM Press, 2013)
This book addresses integration of knowledge and prospects of reviving and renewal of the Islamic religious thought.